Izglītojošā pētniecība skolas fizikas mācību priekšmetā - Mediņa, Dina (Latvijas Universitāte, 2013)
Darba mērķis ir apzināt izglītojošās zinātniskās pētniecībassūtību un būtību fizikas priekšmeta īstenošanā vispārizglītojošā skolā. Diplomdarba galvenais rezultāts ir izvēlētās fizikas priekšmeta programmas tēmas realizācijas kompleksa plānojuma projekts, kurā, akcentējot izglītojošās pētniecības ieviešanas, izstrādāts skolas stundu satura un metodiskais nodrošinājums,kā arī skolēnu sasniegumu (starprezultātu un gala rezultātu)vērtēšanas metodika. Atslēgas vārdi: zinātniskā pētniecība, fizikas priekšmets, izglītojošā zinātniskā pētniecība, pedagoģiskā procesa efektivitāte, skolēnu zināšanu vērtēšana.

Graduation thesis Educational Research was worked out in the Faculty of Education, Psychology and Art of the University of Latvia, Adult Education Centre in collaboration with the Faculty of Physics and Mathematics of the University of Latvia. The thesis contains 42 pages - Introduction (1 page), two parts (19 and 15 pages), Conclusion (2 pages), as well as the List of references (23 sources) and the Supplement (7 units). 5 drawings and 23tables are inserted. The aim of the thesis is to identify the mission and essence of the educational scientific research to be used in the implementation of physics subject in comprehensive school. In Part 1 the existing thematic materials have been identified in the aspect of their content and methodology, especially emphasizing the implementation of educational scientific research methodology in modern comprehensive school. In Part 2 the aim to work out the co was carried out. In addition the realization of this content and the methodology of learning assessment has been developed. Practical realization project of the topic has been worked out within the selected Physics subject program. The efficiency of the elaboration has been partially approved in the pedagogical process. Conclusions and proposals for the further development and improvement of the elaboration have been prepared. The main result of the diploma thesis is a complex project how to realize the chosen physics subject topic in which (with a special emphasis on the educational research) the content of lessons and methodological provision, as well as the assessment methodology of pupils' achievements (both sub result and final result), have been worked out. Key words: scientific research, physics subject, educational scientific research, efficiency of pedagogical process, assessment of pupils achievements.
Educational research in the physics course in school
Keywords: Pedagoģija